MONTHLY AND SEASONAL DYNAMICS OF DEATH CASES CAUSED BY THE DISEASES OF THE CIRCULATORY SYSTEM IN BAKU - V. A. Azizov; E. M. Hatamzadeh; Sh. S. Ibrahimova; L. G. Efendiyeva; T. A. Sadygova (Евразийский Кардиологический Журнал, 2016)
Purpose: to assess the dynamics of the seasonal risk of death cases in metropolis on example of Baku city. Materials: medical certificates of all death cases registered in Baku during 2013 year (totally 12241, including 7971 cases connected diseases of the cir-culatory system). Methods: descriptive statistics of the average daily death cases, analysis methods of quality share signs of the circulatory system diseases amoung causes of death, correlation and regression of the relationship between with the possibility of death and the seasonal dynamics. Results: average monthly cases of death from all reasons and from BCSD made respectively: 1020±34,2 and 664,3±28,3. BCSD share among causes of death in a year made 65,1±0,4%. Average daily quantities of death cases from all reasons and from BCSD respectively made: 33,5±1,24 and 21,8±1,04. Higher than a median (33,4) average daily cases of death from all reasons were observed in February (43,0), March (37,2), April (34,9) and November (36,5). Above a median average daily cases of death owing to BCSD (20,0) were noted in February (29,3), March (24.3) , April (26,6), June (25,5), October (20,1) and November (20.4) . Average daily cases of death from all reasons for winter and spring period (35,8±1,57) statistically significantly (Р